In silico screening of ethyl 4-[(E)-(2-hydroxy-4-methoxyphenyl)methyleneamino]benzoate and some of its derivatives for their NLO activities using DFT - Dinyuy Emmanuel Kiven; Nyiang Kennet Nkungli; Stanley Numbonui Tasheh; Julius Numbonui Ghogomu (Royal Society Open Science, 2023)
The nonlinear optical (NLO) properties of ethyl 4-[(E)-(2-hydroxy-4-methoxyphenyl)methyleneamino]benzoate (EMAB) and some of its derivatives are investigated herein using the density functional theory (DFT) and time-dependent (TD)-DFT methods. The density functionals B3LYP, CAM-B3LYP, M06-2X and ωB97XD, and basis sets 6-31 + G**, 6-311 + + G** and Def2-TZVPP have been used. From the results, EMAB and its substituted derivatives studied are promising candidates for NLO materials. In all cases, the static first and second hyperpolarizabilities (31.7–86.5 × 10−30 and 84.4–273 × 10−36 electrostatic units (esu), respectively) and the frequency-dependent NLO properties are found to be significantly larger (about 43–103 and 28–76 times greater) than those of the NLO prototypical molecule, para-nitroaniline. Furthermore, the maximum absorption wavelengths of the molecules fall within the UV region of the electromagnetic spectrum. Relative to EMAB, the derivatives have shown improved transparency–nonlinearity trade-offs. Natural bond orbital (NBO) and density of states (DOS) analyses herein revealed effective charge transfer within the molecules studied, especially those with stronger electron donors than that in EMAB (methoxy group). Among the molecules studied, the derivative obtained by substituting EMAB's methoxy group with the pyrrolyl group was found to exhibit the best NLO properties. Conclusively, the NLO activities of EMAB can be significantly improved through the substitution of its methoxy group with stronger electron donors.